Click here to kill everybody : security and survival in a hyper-connected world - Schneier, Bruce, 1963- (W.W. Norton & Company, 2018)
"The internet is powerful, but it is not safe. As "smart" devices proliferate the risks will get worse, unless we act now. From driverless cars to smart thermostats, from autonomous stock-trading systems to drones equipped with their own behavioral algorithms, the internet now has direct effects on the physical world. While this computerized future, often called the Internet of Things, carries enormous potential, best-selling author Bruce Schneier argues that catastrophe awaits in its new vulnerabilities and dangers. Forget data theft: cutting-edge digital attackers can now literally crash your car, pacemaker, and home security system, as well as everyone else's. In Click Here to Kill Everybody, Schneier explores the risks and security implications of our new, hyper-connected era, and lays out common-sense policies that will allow us to enjoy the benefits of this omnipotent age without falling prey to the consequences of its insecurity. From principles for a more resilient Internet of Things to a recipe for sane government oversight, Schneier's vision is required reading for anyone invested in human flourishing"--